2022
DOI: 10.1111/ggi.14443
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two scoring methods for the Questionnaire for Medical Checkup of Old‐Old to diagnose frailty

Abstract: judgments, it is necessary to consult the digestive department where gastroscopy can be conducted to confirm further the location of the gastric tube, so as to reduce the risks presented by gastric tube placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It consists of 15 questions related to 10 domains: health status (1 item), mental health (1 item), eating behavior (1 item), oral function (2 items), weight loss (1 item), exercise and falls (3 items), cognitive function (2 items), smoking (1 item), social participation (2 items) and social support (1 item) 9 . The scoring protocol was followed by Shinohara et al ., 19 and the total score was calculated as the sum of all scores.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of 15 questions related to 10 domains: health status (1 item), mental health (1 item), eating behavior (1 item), oral function (2 items), weight loss (1 item), exercise and falls (3 items), cognitive function (2 items), smoking (1 item), social participation (2 items) and social support (1 item) 9 . The scoring protocol was followed by Shinohara et al ., 19 and the total score was calculated as the sum of all scores.…”
Section: Methodsmentioning
confidence: 99%
“…It comprises the following 10 dimensions: health, mental health, eating habits, oral function, weight change, exercise/fall, cognitive function, smoking, social participation, and social support. Previous research has proposed a method of scoring the 15 items of QMCOO with a score of 0 or 1, and frailty is defined by a QMCOO score of ≥4 points [23]. In Japan, the Kihon Checklist is sometimes used as a useful tool for frailty screening [24].…”
Section: Measurementsmentioning
confidence: 99%
“…Their baseline attributes, baseline FSI scores, and QMCOO scores were compared with those of the non-fall group (individuals who did not fall). The FSI score was calculated according to the method described by Yamada et al [18], while the QMCOO score was calculated according to the method described by Shinohara et al [23].…”
Section: Measurementsmentioning
confidence: 99%
“…The questionnaire used in Sato et al's study has demonstrated validity in the incidence of frailty. 2 Based on several previous studies, frailty is a factor associated with fractures. 3 Further, frailty, which is defined by a score ≥4 in this questionnaire, has been shown to have predictive validity for the development of physical disability.…”
mentioning
confidence: 99%
“…Therefore, we remain known whether three items (questions 7-9) in the questionnaire would be appropriate for a robust prediction of fracture occurrence based on previous studies. 2,4 Thus, the significance of this study would be increased by comparing the prediction accuracy, including C-statistics, of each of the 15 items in the questionnaire for fracture occurrence, or the Second, we are concerned about potential measurement error. The authors pointed to the limitations of not distinguishing between past and new fractures.…”
mentioning
confidence: 99%